Avaliação de desempenho e incentivos em uma empresa familiar - Magnago, Barbara Scaramussa (2021)
The use of performance evaluation measurements linked to the granting of incentives aims to ensure that the entire organization's efforts are focused on meeting pre-established strategic goals. However, studies investigating the application of these instruments and their relationship with the monitoring of strategic goals in family businesses produce different results regarding the use or not of these instruments implicitly or explicitly by these companies, highlighting a field of research in the open. In this sense, this research sought to identify how performance evaluation measures are used to track strategic goals and provide incentives in a family business, based on the Agency Theory. Therefore, a single case study was carried out in a family business that operates in the wholesale and distribution sector. For data collection, semi-structured interviews, document analysis, and direct non-participant observation were carried out, and the data were analyzed using Content Analysis. The findings showed that the family is present in the figure of the organization's shareholders, in the board of directors, and the company's presidency, demonstrating that the conduction of the business was delegated to non-family members because the family trusted in the organization's managers. It was also found that the company does not have structured strategic planning, with its goals and objectives arising from the preparation of the annual budget. The studied company uses performance evaluation measures in all its departments. But, as it is a wholesale and distribution company, the commercial department uses these measures with greater emphasis. The results also showed that, contrary to the expectations, this company, despite being familiar, makes little use of subjective measurements of performance, because, as it is a large company, the characteristics bring it closer to a non-family company. It was also found that the company links incentives to the achievement of goals previously established in the commercial department, but the other departments benefit from the incentives based on the financial result achieved. It is concluded, that the use of performance evaluation measures in monitoring the goals is an important mechanism for granting incentives in the researched company. However, it is necessary that these tools also contribute to monitoring the actions of managers to reduce conflicts of interest, as is the case in the company in this case. This research presents theoretical contributions by expanding the understanding of performance evaluation measures and incentives in family businesses. Further demonstrates that the use of "in-house" software to explicitly and formally monitor the company's indicators is demonstrated. In addition, it is possible to observe how the relationship between family and non-family members works in this company. The results can also contribute to managers by helping them to use and implement performance evaluation measurements in family businesses to strengthen relationships within organizations, using incentives as a form of reward.